2021
DOI: 10.1002/ueg2.12132
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of pyogenic liver abscesses in Germany: Analysis of incidence, risk factors and mortality rate based on routine data from statutory health insurance

Abstract: Background Pyogenic liver abscesses (PLAs) represent potentially life‐threatening abdominal conditions that require immediate diagnosis and therapy. European and American incidence figures vary between one and 15 per 100,000 per year. Structured epidemiological data for European countries are not available. Objective To systematically characterize the epidemiology and clinical outcome of PLA in Germany. Methods In representative statutory health insurance data from four million people in 2013–2019, the prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 28 publications
(44 reference statements)
1
19
1
4
Order By: Relevance
“…Pyogenic liver abscess is a common infectious liver disease worldwide with a mortality of 2%-12% 8,9 . It has been estimated that the incidence of pyogenic liver abscess is higher in Asian countries, with approximately 12–18 patients per 100,000 population per year 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyogenic liver abscess is a common infectious liver disease worldwide with a mortality of 2%-12% 8,9 . It has been estimated that the incidence of pyogenic liver abscess is higher in Asian countries, with approximately 12–18 patients per 100,000 population per year 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Pyogenic liver abscess is a common infectious liver disease worldwide with a mortality of 2%-12%. 8,9 It has been estimated that the incidence of pyogenic liver abscess is higher in Asian countries, with approximately 12-18 patients per 100,000 population per year. 10 It has been reported that recently the incidence is increasing due to the application of interventional therapy in hepatobiliary diseases and the aggravation of multidrug resistance in microorganisms, and can further increase in patients with diabetes mellitus or in those receiving immunosuppressive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Die Rezidivrate beträgt etwa 15 %insbesondere bei multiplen oder bilobulären Abszessen (25 % und 36 %), Abszessen durch multiresistente Erreger (46 %) oder vorausgegangenen Cholangitiden (85 %) [35]. Die 1-Jahres-Mortalität wird in Deutschland mit 9 % angegeben und v. a. durch maligne Grunderkrankungen determiniert [11]. Für den Verlauf von KLA liegen noch keine spezifischen…”
Section: Verlauf Und Prognoseunclassified
“…A pyogenic liver abscess (PLA) is pus‐filled cavity within the liver due to a bacterial infection 3 . The annual incidence of PLA has been reported between 1 and 7 cases per 100,000 in some Western Countries and higher among men than women, 4–6 while higher rates have been reported in Taiwan (17.6 per 100,000) with Klebsiella pneumoniae as the primary pathogen 7 . The majority of PLA occurs in patients with pre‐existing gastrointestinal or biliary disease and originates from hematogenous spread though the portal vein.…”
Section: Introductionmentioning
confidence: 99%